ANALYSIS OF THE TEACHERS’ INVOLVEMENT IN THE DISCUSSION OF THE APPLICATION OF THE FEDERAL STATE EDUCATIONAL STANDARDS VIA ONLINE RESOURCES - S N Vachkova (RUDN Journal of Informatization in Education, 2017)
This article presents the research results of the teachers’ involvement extent in current problems emerging in educational activities. The paper discusses the concept of involvement, its functions and scientific approaches to its analysis; suggests the original definition and structure of this concept, describes the chosen methodology of its analysis, database research and the nature of the sample, analysis tools. The base of the present research was the Internet portal “Public expertise of normative documents in education”. There is a detailed description of quantitative results, the indicators of teachers’ participation in discussing problems of education in relation to normative educational documents of Federal state educational standards of primary, basic and secondary general education. The research results showed the indicators of teachers’ activity and the expressed problems in application the Federal state educational standards.